1997
DOI: 10.1165/ajrcmb.16.5.9160833
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and eosinophil responses in the lung, peripheral blood, and bone marrow compartments in a murine model of allergen-induced airways inflammation.

Abstract: Selective accumulation of eosinophils and activated CD4+ cells is now considered a central event in the pathogenesis of asthma, and this process is thought to be mediated by a number of cytokines including tumor necrosis factor-alpha (TNF-alpha), granulocyte-macrophage colony-stimulating factor (GM-CSF), and the Type 2 cytokines interleukin-4 (IL-4) and IL-5. To carry out a detailed time-course analysis of cellular changes in the bronchoalveolar lavage fluid (BAL), peripheral blood (PB), and bone marrow (BM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
173
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(195 citation statements)
references
References 32 publications
19
173
1
Order By: Relevance
“…3). This finding confirms previous experiments using C57BL/6 mice (21) as well as BALB/c mice (4,20). The increased number of immature eosinophils is clearly evident the day after three allergen exposures, in line with the increased BrdU staining in the airways at this time point, suggesting that the eosinophilopoietic response in the bone marrow takes some days to develop.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3). This finding confirms previous experiments using C57BL/6 mice (21) as well as BALB/c mice (4,20). The increased number of immature eosinophils is clearly evident the day after three allergen exposures, in line with the increased BrdU staining in the airways at this time point, suggesting that the eosinophilopoietic response in the bone marrow takes some days to develop.…”
Section: Discussionsupporting
confidence: 93%
“…administration is that the number of eosinophils in the bone marrow is reduced, and the number of eosinophils in the circulation is increased (54). A similar effect is also seen with a single-day allergen exposure (4,19). Recent studies using an in situ bone marrow perfusion model have shown that IL-5 stimulates mobilization of eosinophils from the bone marrow (55,56).…”
Section: Discussionmentioning
confidence: 89%
“…Serum was obtained by centrifugation after incubating whole blood for 30 min at 37°C, and stored as aliquots at Ϫ20°C. BAL was performed, as previously described (43). Briefly, the lungs were dissected and the trachea was cannulated with a polyethylene tube (BD Biosciences).…”
Section: Serum Collection and Bronchoalveolar Lavage (Bal)mentioning
confidence: 99%
“…Each of these assays has a threshold of detection between 1.5 and 5 pg/ml. Levels of OVA-specific serum IgE and IgG1 were measured, as previously described (37,43). Units of OVA-specific Igs were determined relative to in-house standardized serum, obtained from mice sensitized to OVA through conventional i.p.…”
Section: Cytokine and Ig Measurementmentioning
confidence: 99%
“…[5][6][7][8][9][10] However, these responses have typically been assessed in isolation from each other. We have recently demonstrated that C57BL/6J mice undergo a biphasic response to aerosolized ovalbumin (OVA) exposure.…”
mentioning
confidence: 99%